Namibia : 2007 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Namibia. (IMF Staff Country Reports; Country Report, 2008)
Namibia's economic position has been reinforced since the last consultation. The government strategy of broadening the economic base and reducing unemployment while preserving a solid fiscal position is commended. Namibia has ensured that interest rate differentials with South Africa do not destabilize official reserves or capital flows within the common monetary area. The banking system is profitable and well capitalized. Efforts are being made to increase employment opportunities in the non-mining economy by making the labor market more flexible and continuing liberalization of the trade regime.